The Sanctity of The Human Body and The Compulsion of Corona Vaccinations: Study of the Ministry of the Interior and International - Muhammad Saeed Farhad Shakir; Azad Siddiq Muhammad Al-DahZayi; Yassin Maysir Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Among the medical conditions that affect the human body, which have recently arisen and have raised a lot of confusion and debate, it is mandatory to give anti-coronavirus drugs to individuals, which raised a distinct legal question that our research is trying to answer, which is whether the authorities can force individuals to take these vaccines, and whether this compulsion contradicts The original legal principle of the prohibition of touching the human body except with explicit personal consent? The considered legal opinion makes the outbreak of the Corona epidemic an application of the state of necessity stipulated by almost most of the laws of the world. The issue of vaccination against the Corona epidemic must be removed from philosophical discussions about freedom and the pattern of human rights over his body and focus on the realistic health aspect, for the viewer is that every country is late the national immunization program has paid a heavy price in lives.